2013
DOI: 10.1186/1471-2458-13-414
|View full text |Cite
|
Sign up to set email alerts
|

Mental illness in metropolitan, urban and rural Georgia populations

Abstract: BackgroundMental illness represents an important public health problem. Local-level data concerning mental illness in different populations (e.g., socio-demographics and residence – metropolitan/urban/rural) provides the evidence-base for public health authorities to plan, implement and evaluate control programs. This paper describes prevalence and covariates of psychiatric conditions in Georgia populations in three defined geographic areas.MethodsData came from the Georgia population-based random-digit-dialin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
1
12
2
Order By: Relevance
“…Prior literature evaluating mental health disparities in adulthood by place of adult residence, rural versus nonrural areas, has shown equivocal results . Aspects of geographic context that affect mental health may differ across both context (country) and time (birth cohorts and life course period of exposure).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Prior literature evaluating mental health disparities in adulthood by place of adult residence, rural versus nonrural areas, has shown equivocal results . Aspects of geographic context that affect mental health may differ across both context (country) and time (birth cohorts and life course period of exposure).…”
Section: Discussionmentioning
confidence: 98%
“…Prior literature evaluating mental health disparities in adulthood by place of adult residence, rural versus nonrural areas, has shown equivocal results. [47][48][49] Aspects of geographic context that affect mental health may differ across both context (country) and time (birth cohorts and life course period of exposure). For example, three US-based studies included in a recent meta-analysis suggested lower prevalence of depression among rural versus urban older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of urban residency was also evident for psychotic disorders at large and for “psychotic-like symptoms” in different studies from several different regions of the world (Kelly et al, 2010; Szoke et al, 2014; van Os et al, 2001). In addition, some studies reported positive association between urbanicity and development of other mental disorders, such as bipolar disorder (Paksarian et al, 2014), post-traumatic stress disorder (Reeves et al, 2013), depression and anxiety symptoms (Lundberg et al, 2009) but contradicting findings also exist (Baxter et al, 2006; Breslau et al, 2014). …”
Section: Gene-environment Interplaymentioning
confidence: 99%
“…32,38 Peen and colleagues (2010) conducted a large-scale meta-analysis of international studies across 16 developed nations, spanning 25 y. 34 Pooled total prevalence rates for psychiatric disorders were significantly higher for urban settings compared with rural areas, a finding that was consistent across total disorders, mood disorders, and anxiety disorders.…”
Section: Urbanicitymentioning
confidence: 99%
“…Specific to PTSD rates in the United States, Reeves and colleagues (2013) 41 compared metropolitan Atlanta to urban (moderate size metropolitan areas) and rural areas in the state of Georgia. PTSD rates were significantly higher for both urban and rural areas compared with the Atlanta metropolitan area.…”
Section: Urbanicitymentioning
confidence: 99%